2015
DOI: 10.1155/2015/856707
|View full text |Cite
|
Sign up to set email alerts
|

Tolerogenic Dendritic Cells on Transplantation: Immunotherapy Based on Second Signal Blockage

Abstract: Dendritic cells (DCs), the most important professional antigen-presenting cells (APC), play crucial role in both immunity and tolerance. It is well known that DCs are able to mount immune responses against foreign antigens and simultaneously tolerate self-antigens. Since DCs can be modulated depending on the surrounding microenvironment, they can act as a bridge between innate and adaptive immunity. However, the mechanisms that support this dual role are not entirely clear. Recent studies have shown that DCs c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 168 publications
0
12
0
Order By: Relevance
“…Recent evidence highlights the pivotal role of the T cell co‐receptor PD‐1 and its ligands PD‐L1 and PD‐L2 in maintaining an immunosuppressive tumour microenvironment. In addition, it has been reported that PD‐L1 blockade improves anti‐tumour immunity and represents one approach for cancer immunotherapy . The PD‐1‐related pathway also plays a specific role in the suppression of imDCs during the establishment of tolerance, as PD‐1 and PD‐L1/PD‐L2 signalling form a co‐inhibitory pathway that contributes to the negative regulation of T lymphocyte activation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence highlights the pivotal role of the T cell co‐receptor PD‐1 and its ligands PD‐L1 and PD‐L2 in maintaining an immunosuppressive tumour microenvironment. In addition, it has been reported that PD‐L1 blockade improves anti‐tumour immunity and represents one approach for cancer immunotherapy . The PD‐1‐related pathway also plays a specific role in the suppression of imDCs during the establishment of tolerance, as PD‐1 and PD‐L1/PD‐L2 signalling form a co‐inhibitory pathway that contributes to the negative regulation of T lymphocyte activation .…”
Section: Discussionmentioning
confidence: 99%
“…ImDCs remain immature and sessile within the epidermis and have a relatively low T cell stimulatory ability, while mDCs egress to initiate immune responses. The antigen‐presenting ability of DCs can be obstructed by impairing their function through changing the expression of co‐stimulatory molecules . Thus, the maturation state of DCs might be one of the important control points for anti‐tumour immunotherapy .…”
Section: Introductionmentioning
confidence: 99%
“…Successful pursuit of these applications requires fully understanding the factors influencing DC maturation and function 7 10 , as well as the soluble factors that mediate their effects on T cells and other immune cells 11 . Agents that repress DC costimulatory molecule expression confer a tolerogenic DC phenotype 12 , 13 . Further, there is increasing appreciation of the importance of intracellular enzymes such as heme oxygenase-1 (HO-1) and soluble, secreted factors that range from the HO-1 enzymatic reaction product carbon monoxide (CO) 14 16 , to suppressive cytokines such as transforming growth factor-beta (TGF-β) 17 , IL-10, and other modulators of vascular and lymphocyte function, such as endothelin-1 (EDN-1) 18 .…”
Section: Introductionmentioning
confidence: 99%
“…TolDCs also play an important role in maintaining grafted organs ( 82 83 84 85 ). As in the treatment of autoimmune disorders, the use of immunosuppressive drugs has been a dominant treatment method for transplantation recipients.…”
Section: Therapeutic Applications Of Toldcsmentioning
confidence: 99%